2020
DOI: 10.1038/s41537-020-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotion awareness and regulation on psychotic symptoms during daily functioning

Abstract: Emotion regulation (ER) difficulties are ubiquitous among individuals with schizophrenia and have been hypothesized to contribute to stress sensitivity and exacerbation of psychotic symptoms in this population. However, the evidence supporting this link is equivocal, potentially due to previous studies' reliance on retrospective assessments of ER and psychosis, as well as lack of consideration of putative moderators such as emotion awareness. To address these limitations, we employed experience sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…Our results are in line with previous evidence of greater attention to emotions in healthy individual with schizotypal personality (Kerns, 2005). On the other hand, reduced emotional awareness is typically observed in individuals at clinical high-risk for psychosis (e.g., van Rijn et al, 2011) and among psychotic patients (e.g., Kimhy et al, 2012Kimhy et al, , 2020. This suggests that these deficits could be specific to individuals with clinicallyrelevant manifestations of psychosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with previous evidence of greater attention to emotions in healthy individual with schizotypal personality (Kerns, 2005). On the other hand, reduced emotional awareness is typically observed in individuals at clinical high-risk for psychosis (e.g., van Rijn et al, 2011) and among psychotic patients (e.g., Kimhy et al, 2012Kimhy et al, , 2020. This suggests that these deficits could be specific to individuals with clinicallyrelevant manifestations of psychosis.…”
Section: Discussionsupporting
confidence: 92%
“…Reappraisal is commonly considered a functional emotion regulation strategy (Webb et al, 2012), but recently it was discussed that its use is not always beneficial (Ford & Troy, 2019). Some studies have even found reappraisal to be associated with more pronounced paranoid thoughts (Kimhy et al, 2020;Westermann et al, 2012) and to increase negative affect during psychotic experiences (Strauss et al, 2019). For determining the functionality of reappraisal, the reappraised thought contents and the context, in which it is used, may need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…We also included the Emotion Contagion Scale ( 28 ) to look at mirroring or emotional resonance with others. Furthermore, we included the Toronto Alexithymia Scale ( 29 , 30 ), as alexithymia (i.e., difficulties with identifying and describing internal emotional states) may in turn influence social cognition ( 31 ) and can be seen in disorders associated with magical thinking [OCD ( 16 , 32 , 33 ); schizophrenia ( 34 , 35 )]. In order to explore which factors may mediate the relationship between TAF and empathy, we included a couple of other scales relevant to conditions such as OCD and schizophrenia that are likely to be related to magical thinking.…”
Section: Introductionmentioning
confidence: 99%